RESINAS INFILTRANTES PARA EL MANEJO ESTÉTICO Y FUNCIONAL DE LESIONES DEL ESMALTE:REVISIÓN DE REPORTE DE CASOS Y SERIES DE CASOS - Ordoñez Romero, Ingrid Rosalyn (2025)
Objective: To analyze the available evidence from case reports and case series on the use of resin infiltration as a microinvasive technique for the esthetic and functional management of various enamel defects. Materials and Methods: A literature review was conducted through searches in PubMed, SciELO, and BVS, including open-access articles published between 2011 and 2025. A total of 23 articles consisting of case reports and case series were selected, describing resin infiltration protocols, technical variations, and clinical outcomes. Results: Resin infiltration demonstrated immediate masking and significant esthetic improvement in most enamel lesions. Protocols were homogeneous, typically involving 15% hydrochloric acid etching, ethanol desiccation, and prolonged application of the infiltrant. Variations such as repeated etching, extended infiltration times, or combined therapies proved beneficial for deep or pigmented lesions. Studies reported stability ranging from 1 to 8 years, with high patient satisfaction and minimal invasiveness. Conclusions: Resin infiltration is a conservative alternative with favorable clinical performance and reliable esthetic outcomes for the management of multiple enamel alterations, provided that appropriate case selection is performed and a rigorous clinical protocol is applied.